Understanding energy contributions in cycling - Giorgi, H. (Elite Training Seminar Series, 2017)
Understanding the different components of a movement or sport on which athletes spend energy provides coaches with practical information related to training load quantification, testing protocols, equipment and technique changes, alterations to physique, and predictions of athletes` performances. My PhD was one of the first embedded sport-based PhDs at the Queensland Academy of Sport in Brisbane, Australia, and although it was primarily concerned with the various energy contributions in cycling, the theoretical basis can be applied to other sports - similar projects have since been conducted in swimming and rowing, for example. A strength of such investigations is their multidisciplinary nature, drawing together physiological and biomechanical approaches to sport science.